1999
DOI: 10.3168/jds.s0022-0302(99)75405-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Accelerated Growth Rates and Estrogen Implants in Prepubertal Holstein Heifers on Growth, Feed Efficiency, and Blood Parameters

Abstract: Sixty-eight Holstein heifers were used to determine the effects of accelerated growth rates by increased nutrient intake and estrogen implants on feed efficiency, structural growth, and blood parameters in heifers between 19 and 39 wk of age. At the beginning of the treatment period, the heifers were assigned to one of four treatment groups by using a randomized complete block design in a 2 x 2 factorial arrangement. The treatments were standard growth rate (700 g/d), accelerated growth rate (1000 g/d), standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Additionally, it is not clear whether muscle IGF‐I mRNA levels are increased by direct action of E 2 and/or TBA or whether IGF‐I mRNA levels are elevated as an indirect response to steroid‐induced changes in the level of some other growth factor such as somatotropin. The potential role of somatotropin is of particular interest since there are conflicting reports as to whether circulating somatotropin levels are increased by steroid implantation (Hunt et al, 1991; Hayden et al, 1992, 1993; Lammers et al, 1999; Hassanab et al, 2001). Our current data demonstrate that IGF‐I mRNA levels are increased by treating proliferating BSC cultures with either E 2 or trenbolone; thus, establishing that these steroids directly stimulate production of IGF‐I in these cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is not clear whether muscle IGF‐I mRNA levels are increased by direct action of E 2 and/or TBA or whether IGF‐I mRNA levels are elevated as an indirect response to steroid‐induced changes in the level of some other growth factor such as somatotropin. The potential role of somatotropin is of particular interest since there are conflicting reports as to whether circulating somatotropin levels are increased by steroid implantation (Hunt et al, 1991; Hayden et al, 1992, 1993; Lammers et al, 1999; Hassanab et al, 2001). Our current data demonstrate that IGF‐I mRNA levels are increased by treating proliferating BSC cultures with either E 2 or trenbolone; thus, establishing that these steroids directly stimulate production of IGF‐I in these cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of estrogens in aquatic environments has recently been reported [3][4][5]. In addition, some estrogens that are used in the animal feeds promote growth rate and enhance fat deposition of animals [6]. Estrogenic hormones, such as 17␤-estradiol (E2), estrone (E1) and estriol (E3), exhibit high degrees of estrogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical elevation of PUN observed when E 2 was administered to steers consuming the control diet is very small and is considered within normal variation. Lammers et al (1999) observed an 11% decrease in PUN concentration in prepubertal heifers fed for growth rates of either 700 or 1000 g d -1 and implanted with E 2 .…”
Section: Blood Parametersmentioning
confidence: 85%